An assessment on sales promotional activities as key fundamentals in the improvement of a company performance: a case of BIMCO in Redcliff - Marambi, Emmanuel (Midlands State University, 2015)
The study sought to analyse the sales promotional activities as key fundamentals in the improvement of BIMCOs’ performance. The objectives of the study were to: identify the sales promotional activities being used by BIMCO, to determine the impact of sales promotional activities on sales turnover, to determine the impact of sales promotional activities on market share, to determine the impact of sales promotional activities on customer retention, to establish weaknesses of the current promotional activities and finally to identify other factors other than sales promotional activities that can improve on the company’s’ performance. The literature review was used to gain a more in-depth knowledge of the researched problem. The descriptive research design was used to review literature from different authors and websites in relation to the sales promotional activities to improve the organisation. The literature review chapter will focus on the following subtopics: the definition of sales promotional activities, the objectives of sales promotional strategies, growth of sales promotion, some types of promotional activities, impact of sales promotion on company performance, other factors that influence changes in company performance and the summary of the chapter. The representative population was the employees and customers (credit and cash) in Zimbabwe. The researcher used descriptive and exploratory research. The data used was collected through questionnaires and secondary data sources and a sample of 30 individuals who included both employees and customers at BIMCO. 20 questionnaires were distributed and 15 were returned, giving a response rate of 75% and 10 interviews were carried out and 8 were successful giving a response rate of 80%. Questionnaires and interviews were used as data collection instruments. Microsoft Excel was used in data presentation. In the analysis and interpretation, frequencies, percentages was used and closed and open ended questions were used to gather data from the respondents. Presentation then followed through the use of tables, in an attempt to make the data usable by decision makers. Data collected from the respondents was presented in the form of tables, bar graphs and pie charts. The data was also analysed and interpreted in a descriptive way. In view of the findings of the research study, it is evidenced that price discounts, exhibitions and free samples are the most common sales promotional activities being used by BIMCO. The findings revealed that the company’s current sales promotional activities are ineffective therefore there is need to improve the promotional activities to cub the problem accruing for not improving the company performance. The findings also revealed that, other factors to consider that might help in improving the companies’ performance include the price, quality, brand image, flexibility of payment terms, advertisements as well as skills training. On the conclusions the sales promotional activities currently in use at BIMCO may not be effective in improving company performance as they have a relatively low influence to the variations in sales performance. It was observed in the study that BIMCO is not concurrently active in sales promotion and yet maintain higher sales volume and profitability. The researcher recognized that sales promotion has a great impact on customers and performance of the organisation as well. Irrespective of the sales increasing it is short lived because there is excitement among customers on price discounts. Recommendations are also suggested for the improvement of the current problem. A number of strategies were recommended which include adding more sales promotion activities, knowing when it is time to use promotional activities and on-the-job training for employees to enhance their experience. Since it has immerged that sales promotion alone can not increase the company’s market share, it is recommended that the company should produce quality products for their customers. For BIMCO to avoid customers from switching brands unnecessarily, the organisation should embrace more relationship strategies.